Hearing loss in survivors of childhood head and neck rhabdomyosarcoma: a long‐term follow‐up study. (8th February 2016) - Schoot, R.A.; Theunissen, E.A.R.; Slater, O.; Lopez‐Yurda, M.; Zuur, C.L.; Gaze, M.N.; Chang, Y.‐C.; Mandeville, H.C.; Gains, J.E.; Rajput, K.; Pieters, B.R.; Davila Fajardo, R.; et al.
Abstract : Objectives: To determine the hearing status of survivors treated for head and neck rhabdomyosarcoma (HNRMS) at long‐term follow‐up. Design: Cross‐sectional long‐term follow‐up study. Setting: Tertiary comprehensive cancer centre. Participants: Survivors treated for HNRMS during childhood in two concurrent cohorts; survivors in London had been treated with external beam radiotherapy (EBRT‐based local therapy); survivors in Amsterdam were treated with AMORE (Ablative surgery, MOuld technique afterloading brachytherapy and surgical REconstruction) if feasible, otherwise EBRT (AMORE‐based local therapy). Main outcome measures: We assessed hearing status of HNRMS survivors at long‐term follow‐up. Hearing thresholds were obtained by pure‐tone audiometry. Methods: We assessed the hearing thresholds, the number of patients with clinically relevant hearing loss and hearing impairment graded according to the Common Terminology Criteria for Adverse Events version 4.0 (CTCAEv4) and Boston criteria. Furthermore, we compared hearing loss between survivors treated with EBRT‐based local therapy (London) and AMORE‐based local therapy (Amsterdam). Results: Seventy‐three survivors were included (median follow‐up 11 years). We found clinically relevant hearing loss at speech frequencies in 19% of survivors. Multivariable analysis showed that survivors treated with EBRT‐based treatment and those with parameningeal tumours had significantly more hearing impairment, compared to survivors treated with AMORE‐based treatment and non‐parameningeal tumours. Conclusions: One in five survivors of HNRMS developed clinically relevant hearing loss. AMORE‐based treatment resulted in less hearing loss compared to EBRT‐based treatment. As hearing loss was highly prevalent and also occurred in survivors with orbital primaries, we recommend systematic audiological follow‐up in all HNRMS survivors.